Influence of fired clay brick waste additions on the durability of mortars. (September 2015) - Schackow, A.; Stringari, D.; Senff, L.; Correia, S.L.; Segadães, A.M.
Abstract: The use of metakaolin is known to help improve properties of Portland cement-based mortars. The presumed similarities between the characteristics of metakaolin and those of a powdered (<45 μm) fired clay brick clean waste (CBW) led to the investigation of the effect on the durability of mortars of partial replacement (10, 25 and 40 wt.%) of Portland cement by CBW. Properties such as 28 and 90 days-compressive strength, water absorption, apparent porosity, absorption by capillarity, chloride retention, carbonation depth and sulphate resistance were evaluated. The CBW-containing cured mortars showed improved strength and density, as the result of combined physical and pozzolanic pore filling effect of added CBW. However, CBW-free mortar exhibited larger spreading and, being more porous, higher sulphate resistance and ability to absorb chlorides. Optimum performance was found for the 40 wt.% CBW mortar whose compressive strength can be up to 130% higher than that of the CBW-free mortar.